2001
DOI: 10.1021/ja011729q
|View full text |Cite
|
Sign up to set email alerts
|

An NMR Investigation of CO Tolerance in a Pt/Ru Fuel Cell Catalyst

Abstract: We report the first combined application of solid-state electrochemical NMR (EC NMR), cyclic voltammetry (CV), and potentiostatic current generation to investigate the topic of the ruthenium promotion of MeOH electro-oxidation over nanoscale platinum catalysts. The CV and EC NMR results give evidence for two types of CO: CO on essentially pure Pt and CO on Pt/Ru islands. There is no NMR evidence for rapid exchange between the two CO populations. CO molecules on the primarily Pt domains behave much like CO on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
321
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 357 publications
(348 citation statements)
references
References 21 publications
(32 reference statements)
23
321
2
2
Order By: Relevance
“…9 The latter topic is also of interest in the context of fuel cell catalysis, but there has been no direct experimental determination of D CO in an electrochemical environment due to problems associated with the presence of the electrolyte. 10 Fortunately, however, NMR methods are not plagued by these problems, [11][12][13] and in this paper, we report the first direct determination of the diffusion constants of CO on Pt in a liquid electrochemical environment, together with the activation energy for diffusion, using the techniques of electrochemical NMR (EC-NMR) 11-14 and selective spin inversion NMR. 7 To determine diffusion constants, we used the "S-shape" pulse sequence developed by Becerra et al 7 The S-shape pulse sequence (Figure 1) exploits the fact that CO molecules adsorbed on a Pt nanoparticle can have different 13 C resonance frequencies, depending on the angle of CO's unique molecular axis with respect to the external magnetic field.…”
mentioning
confidence: 91%
“…9 The latter topic is also of interest in the context of fuel cell catalysis, but there has been no direct experimental determination of D CO in an electrochemical environment due to problems associated with the presence of the electrolyte. 10 Fortunately, however, NMR methods are not plagued by these problems, [11][12][13] and in this paper, we report the first direct determination of the diffusion constants of CO on Pt in a liquid electrochemical environment, together with the activation energy for diffusion, using the techniques of electrochemical NMR (EC-NMR) 11-14 and selective spin inversion NMR. 7 To determine diffusion constants, we used the "S-shape" pulse sequence developed by Becerra et al 7 The S-shape pulse sequence (Figure 1) exploits the fact that CO molecules adsorbed on a Pt nanoparticle can have different 13 C resonance frequencies, depending on the angle of CO's unique molecular axis with respect to the external magnetic field.…”
mentioning
confidence: 91%
“…Shape-controlled synthesis of Pt nanocubes, which are enclosed by (100) surfaces, has therefore received great attention as high-performance electrocatalysts [16,25,26]. More excitingly, incorporation of other metals into the Pt NPs to form bimetallic Pt NPs has been proved to be a promising method for further enhancing the catalytic properties due to the bifunctional mechanism [27] and the electronic effect [28,29]. For instance, Xu et al [30] demonstrated that Pt 80 Cu 20 nanocube catalyst was about ten times more durable than its Pt nanocube counterpart for formic acid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Using Pt/C ETEK, the diffusion limit mass current density for the ORR was 20 % smaller than that using the same electrocatalyst without ethanol. These results can be explained because the strength of adsorption of both CO (Tong, Kim et al, 2002;Alayoglu, Nilekar et al, 2008;Park, Lee et al, 2008) and O 2 (Min, Cho et al, 2000;Aricò, Shukla et al, 2001;Shukla, Neergat et al, 2001;Lima, Lizcano-Valbuena et al, 2006) is reduced in Pt 3 Sn alloy materials, thereby facilitating a release of the catalytic sites and increase of the kinetic reaction.…”
Section: Electrochemical Experimentsmentioning
confidence: 99%
“…Its high performance is because the electronic interactions between Pt and the alloyed metals modify the lattice parameters of platinum, leading to a change in the electron density of the material by shrinking of the "d" band of platinum (electronic effect) (Tong, Kim et al, 2002;Alayoglu, Nilekar et al, 2008;Park, Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%